RSM Analysis of In-cylinder Pressure in a DICI Engine Fueled with Argemone Mexicana Biodiesel-diesel Blends - K. Parida, M.; Routaray, I. (International Journal of Engineering and Technology, 2018)
In the current analysis engine load, compression ratio and bio-diesel blends are taken as input parameters to evaluate the combustion parameter i.e maximum in cylinder pressure with methyl esters of Argemone Mexicana and its diesel blends in a VCR multi-fuel engine. Response surface method of Full Factorial Design (FFD) is used in the present study for modelling and analyzing the combustion parameter with Minitab-14.0 software. The response surface and contour plots of different models are plotted by holding mean value of other input parameter. The developed model, data regression, significance analysis and individual model coefficients were studied and presented for model validation.